PENINGKATAN KETERAMPILAN MENULIS TEKS NEGOSIASI MENGGUNAKAN MODEL EXAMPLE NONEXAMPLE PADA SISWA SMAK - yarso, Elanatasia; Salem, Laurensius; Patrianto, Patrianto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is initiatedby the lack of student skills in writing. This can be proved from the average student's scorewhichis below 70; the criteria of minimal submission, the students are less skilled in pouring ideas into their writing. This research is focused on writing material on negotiating text using an example nonexample learning model. The problem formulated in this study,